Stage of cancer diagnoses among migrants from the former Soviet Union in comparison to the German population - are diagnoses among migrants delayed? - Cho, An Bin; Jaehn, Philipp; Becher, Heiko; Winkler, Volker (BMC public health, 2018)
In this study, we compared stage at diagnosis, standardized incidence ratio (SIR) and standardized mortality ratio (SMR) of most frequent cancer diagnoses between re-settlers (Aussiedler) from the former Soviet Union and the general population in the Saarland in Germany to assess possible delays in diagnosis of cancer among this migrant group.